Analisis Strategi Bisnis PT. Asuransi Jiwa Inhealth Indonesia - Retnofia Chaira; Syukri Lukman; Hendra Lukito (SAFE-Network, 2023)
The purpose of this research is to analyze the business strategy of PT. Asuransi Jiwa Inhealth Indonesia. The research was carried out in an effort to identify the company's external and internal factors, and then determine a strategy using SWOT Analysis, Space Matrix and QSPM Matrix. The scope of research includes the external environment with PESTEL and the internal environment which consists of aspects that exist within the company. The population in this study are L3 and L2 managers at the service office level throughout Indonesia. The sample in this study used a purposive sample so that a sample of 5 managers and 2 people from external parties was obtained. data collection techniques by conducting interviews. The method used in this research is to use a comprehensive strategic management model. The results of the research based on the TOWS analysis obtained 16 alternative strategies that could be implemented by Mandiri Inhealth. The results of the IE analysis show that the point of intersection between the EFE and IFE analysis scores is in cell V which indicates the right alternative strategy implemented by the company, namely market penetration and product development. The results of the QSPM analysis on it can be concluded that the best strategy implemented by the company is a product development strategy with the highest total QSPM score (6.465). The limitations of this study are that it is based on corporate strategy regulations, uses SWOT analysis, IE Matrix and QSPM, only discusses Health Insurance products and does not use Business Model Canvas (BMC) analysis and also Focus Group Discussion (FGD). Suggestions for future researchers to add analysis using BMC and FGD between divisions so that planning and execution can run well according to the targets set.